2019
DOI: 10.1186/s12906-019-2725-z
|View full text |Cite
|
Sign up to set email alerts
|

Coix lacryma-jobi var. ma-yuen Stapf sprout extract induces cell cycle arrest and apoptosis in human cervical carcinoma cells

Abstract: BackgroundCervical cancer is the second-leading cause of cancer-related mortality in females. Coix lacryma-jobi L. var. ma-yuen (Rom.Caill.) Stapf ex Hook. f. is the most widely recognized medicinal herb for its remedial effects against inflammation, endocrine system dysfunctions, warts, chapped skin, rheumatism, and neuralgia and is also a nourishing food.MethodsTo investigate the activity of Coix lacryma-jobi sprout extract (CLSE) on cell proliferation in human cervical cancer HeLa cells, we conducted a Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Stroke is a major cause of disability and death worldwide, but the agents currently used to treat stroke are not sufficient to effectively improve the recovery of stroke patients [ 25 , 26 ]. Coicis Semen, a traditional Chinese medicine, exerts antioxidant and anti-inflammatory effects in many diseases, including coronary heart disease [ 27 ], systemic inflammatory disease [ 28 ], and cancer [ 9 , 29 ]. In a previous study, Coicis Semen was shown to have an antioxidant effect, and oxidative stress is closely associated with the prognosis of ischemic stroke [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is a major cause of disability and death worldwide, but the agents currently used to treat stroke are not sufficient to effectively improve the recovery of stroke patients [ 25 , 26 ]. Coicis Semen, a traditional Chinese medicine, exerts antioxidant and anti-inflammatory effects in many diseases, including coronary heart disease [ 27 ], systemic inflammatory disease [ 28 ], and cancer [ 9 , 29 ]. In a previous study, Coicis Semen was shown to have an antioxidant effect, and oxidative stress is closely associated with the prognosis of ischemic stroke [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in the treatment time and concentration of BDA-Nb, the proliferation inhibition level increased. Son et al [ 35 ] also observed that the cell proliferation inhibition in the cells treated with Coix lacryma-jobi sprout extract increased in a concentration- and time-dependent manner. Meanwhile, K562 and A549 cells showed abnormal morphological features, including low growth density, nuclear chromatin concentration, condensation, and margination ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance in lymphoid cells for ABT-199 has been documented [ 189 ]. Some diseases are liable to be as dependent on one Bcl-2 protein as CLL; the majority of tumors will likely require combinations of these drugs to have a significant therapeutic impact; however, these combinations may show unacceptable toxicity [ 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 ].…”
Section: Limitations Of Bcl-2 Inhibitorsmentioning
confidence: 99%
“…Bcl-2 is a 26 kDa, 239 amino-acid protein that composes four domains, BH1, BH2, BH3, and BH4 [38,76]. The BH4 domain residues (10-30), BH3 domain residues (93-107), BH1 domain residues (136)(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155), and BH2 domain residues (187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202) [76] (https://www.uniprot.org/uniprot/P10415#structure; accessed on 15 August 2021) (Figure 3A) and the amino acid sequences of the BH1-4 domains of Bcl-2 [76] (Figure 3B) are provided. The structure of a Bcl-2 chimeric protein comprising a truncated loop obtained from Bcl-xL among the Hα1 as well as Hα2 was initially observed through NMR spectroscopy [77].…”
Section: Bcl-2 Structure and Functionmentioning
confidence: 99%